Directional single-mode emission from coupled whispering gallery resonators realized by using ZnS microbelts - Zhu, Hai (2013)
Ring microcavities were formed by wrapping ZnS microbelts, which act as the waveguide and gain region of the microcavities on the surface of optical fibers. The ring microcavities with the formation of whispering gallery modes have lasing threshold lower (Q-factor higher) than that of the ZnS microbelts. The excitation of TM modes could also be suppressed by the ring geometries of ZnS microbelts. Furthermore, directional single-mode lasing was realized from a coupled asymmetric ring microcavity. The Vernier coupling effect and deformed geometry of the asymmetric ring microcavity were contributed to the stable single-mode operation and directional emission, respectively.